2020
DOI: 10.32890/mmj.17.2013.8993
|View full text |Cite
|
Sign up to set email alerts
|

The Formation of Separate Risk Management Committee and the Effect on Modified Audit Report

Abstract: The aim of the paper is to examine the formation of a separate risk management committee (RMC) and its effect on the modified audit report among the non-banking and financial companies listed in Bursa Malaysia. Data was collected from the annual reports of a sample of 300 companies from 2004 until 2009. Both descriptive and multivariate analyses were employed to address the research objectives. The results indicate that a separate RMC is negatively related with the acceptance of the modified audit report. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The results are consistent with other studies that claimed the existence of a stand-alone RMC could increase risk monitoring and reduce agency costs and information asymmetry, hence, leads to higher risk management disclosure quality (Alkilani et al , 2020; Jia, 2017; Jensen and Meckling, 1976). Accordingly, Ishak and Yusof (2013) stated that a separate RMC is likely to foresee and able to evaluate a company's viability in future and reduce the risks of going-concern than depending on the role of the audit committee. This is because the latter committee is viewed to only have the expertise in the internal control and accounting transactions, while lacking the expertise required on the company business's external environment, particularly, on the business opportunity and investment.…”
Section: Theory and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The results are consistent with other studies that claimed the existence of a stand-alone RMC could increase risk monitoring and reduce agency costs and information asymmetry, hence, leads to higher risk management disclosure quality (Alkilani et al , 2020; Jia, 2017; Jensen and Meckling, 1976). Accordingly, Ishak and Yusof (2013) stated that a separate RMC is likely to foresee and able to evaluate a company's viability in future and reduce the risks of going-concern than depending on the role of the audit committee. This is because the latter committee is viewed to only have the expertise in the internal control and accounting transactions, while lacking the expertise required on the company business's external environment, particularly, on the business opportunity and investment.…”
Section: Theory and Literature Reviewmentioning
confidence: 99%
“…Accordingly, Onga et al (2015) also reported that the existence of a RMC in a company might not have a role in preventing restatement practices. Accordingly, prior studies also indicate that the role of the RMC in risk management is relatively unexplored, and the literature in that field is limited and scarce (Ishak and Yusof, 2013). In other words, there is little empirical evidence on both corporate governance and firm-related factors associated with an organisation's decision to set up a separate RMC.…”
Section: Introductionmentioning
confidence: 99%
“…A separate RMC is more likely to foresee and able to evaluate a company's viability in the future and reduce the risks of going-concern than depending on the role of the audit committee. This is because the RMC is viewed to have only the expertise in the internal control and accounting policies, while lacking the expertise required on the company business's external environment, particularly, on the business opportunity and investment (Ishak and Yusof, 2013;Rimin et al, 2021). Therefore, based on this evidence, the tenth hypothesis is as follows:…”
Section: Audit Committee Characteristics and Integrated Reporting Pra...mentioning
confidence: 99%
“…As a risk monitoring tool, the risk management committee is expected to improve the level of risk monitoring, resulting in lower agency costs and less information asymmetry (Jensen & Meckling, 1976). Ishak and Yusof (2014) and Subramaniam et al (2009) argue that a risk management committee could improve the quality of internal risk monitoring for firms. Nahar et al (2020) indicate that the existence of various risk committees and a unit for risk management has a positive relationship with risk disclosure.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%